Path integrals in physics - Chaichian M; Demichev A (Bristol Institute of Physics, 2001)
Volume I deals with systems possessing a infinite number of degrees in freedom. In this case the mathematics behind is well understood. The authors present it in a form accessible to a broad community of theoretical physicists. Various applications, incl
V1: Stochastic processes and quantum mechanics
Keywords: Mathematical physics; Path integrals